An aerogel with high electromagnetic shielding and high electromagnetic absorption performance and an integrated preparation method thereof

By combining aramid nanofibers and conductive two-dimensional nanosheet layer materials with polyamic acid PAA hydrogel and wave absorber, an impedance gradient electromagnetic shielding aerogel with a gradient structure is prepared, which solves the electromagnetic wave reflection problem caused by existing electromagnetic shielding materials and achieves efficient electromagnetic wave absorption and shielding effects.

CN116640353BActive Publication Date: 2025-03-25NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202310336923.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-03-25
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

While existing electromagnetic shielding materials realize electromagnetic wave interference shielding, they will bring a large amount of electromagnetic wave reflection, resulting in serious secondary pollution, especially in high-precision equipment, electromagnetic wave reflection will affect the operation of the equipment.

Method used

Laminated hydrogels are prepared by combining aramid nanofibers and conductive two-dimensional nanosheet layer material and mixed with polyamic acid PAA hydrogel and absorber to form an impedance gradient electromagnetic shielded aerogel with a gradient structure. This method achieves integrated preparation of efficient electromagnetic shielding and absorption structure through vacuum suction filtration and freeze-drying.

Benefits of technology

It realizes high absorption and high shielding characteristics, reduces electromagnetic wave reflection, avoids secondary pollution, and enhances the designability of the material and the electromagnetic wave step by step absorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640353B_ABST
    Figure CN116640353B_ABST
Patent Text Reader

Abstract

The present invention discloses an aerogel with high electromagnetic shielding and high electromagnetic absorption performance and an integrated preparation method thereof, wherein the method is as follows: first, aramid nanofibers and two-dimensional conductive fillers are prepared into a layered high-performance shielding layer by a vacuum filtration method, and then hydrogels with different impedance characteristics are prepared by controlling the solid content of aramid nanofibers and polyimide matrix, and combining the control of the content of absorbing fillers, and this is used as a gradient impedance module; the high-performance shielding layer and the hydrogel modules with different impedance characteristics are stacked and frozen, and a high-absorption electromagnetic shielding aerogel is prepared by freeze drying and thermal imidization. The composite aerogel prepared by the present invention has good mechanical properties, ultra-high broadband electromagnetic wave absorption capacity and efficient electromagnetic shielding performance, as well as excellent heat insulation, sound absorption and other functions, and is suitable for applications in building protection, electronic equipment and aerospace fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of novel aerogel structure design, and in particular to an aerogel with high electromagnetic shielding and high electromagnetic absorption performance and an integrated preparation method thereof. Background Art

[0002] With the rapid development of electronics, communications and other technologies, the electromagnetic pollution problem is becoming more and more serious, which not only harms the operation of electronic equipment and data transmission, but also threatens people's health. In view of the above problems, an effective defense method is to use electromagnetic shielding materials to block the transmission of unnecessary electromagnetic waves. Therefore, exploring efficient electromagnetic shielding materials has become an urgent need for the current social and technological development.

[0003] At present, electronic devices are developing rapidly towards the direction of portability and wearability, and the preparation of flexible and efficient electromagnetic shielding materials has become a current research hotspot. Studies have shown that high-conductivity films (graphene films, MXene films, etc.) can achieve high-performance electromagnetic shielding. However, while achieving electromagnetic wave interference shielding, simple high-conductivity films will bring a large amount of electromagnetic wave reflection, causing serious secondary pollution. Especially in high-precision equipment with a large number of integrated electronics, the emitted electromagnetic waves will seriously affect the operation of the equipment. Therefore, it is of great significance to develop electromagnetic shielding flexible materials with high absorption and high shielding characteristics. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an aerogel with high electromagnetic shielding and high electromagnetic absorption performance and an integrated preparation method thereof, so as to realize the integrated preparation of high-performance electromagnetic shielding and electromagnetic wave absorption structure, and structurally design the absorbing layer with the help of material properties to realize the material's wide-band high absorption and high shielding properties.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0006] (I) The present invention provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0007] S1, vacuum filtering the aramid nanofiber (ANF) dispersion through a microporous filter membrane to obtain a layered aramid nanofiber hydrogel, then adding a conductive two-dimensional nanosheet material, and continuing vacuum filtering to obtain a layered hydrogel with electromagnetic shielding performance;

[0008] S2, taking aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion to mix to prepare ANF / PAA hydrogel, adding absorbent X and stirring evenly to obtain ANF / PAA / X hydrogel with impedance characteristics;

[0009] S3. The layered hydrogel prepared in S1 is stacked with the ANF / PAA / X hydrogel prepared in S2, frozen, and then freeze-dried and thermally imidized to form a highly absorbing electromagnetic shielding aerogel.

[0010] Furthermore, in S1, the conductive two-dimensional nanosheet material is a two-dimensional nanomaterial with high conductivity, specifically graphene and / or MXene.

[0011] Furthermore, in S1, the surface density of ANF in the layered aramid nanofiber hydrogel is 0.4-1.2 mg / cm 2 The mass ratio of the conductive two-dimensional nanosheet material to the aramid nanofiber is 1 to 10:1.

[0012] Furthermore, in S2, one or more groups of ANF / PAA / X hydrogels are prepared; when more than one group of ANF / PAA / X hydrogels are prepared, each group of ANF / PAA hydrogels has a different solid content and / or an amount of absorber added to form several groups of ANF / PAA / X hydrogels with different impedance characteristics as gradient impedance modules.

[0013] Furthermore, in S2, the solid content of the ANF / PAA hydrogel is 0.5wt%-3wt%, and the mass ratio of ANF to PAA is 1:(0-5).

[0014] Furthermore, in S2, the absorber X is one or more of graphene, MXene, carbon nanotubes, carbonyl iron and ferrite; and the mass ratio of the absorber to the ANF+PAA solid is (0-10):(1-2).

[0015] Furthermore, in S3, the ANF surface of the layered hydrogel faces upward, and the ANF surface of the layered hydrogel contacts and fuses with the ANF / PAA / X hydrogel; when more than one group of ANF / PAA / X hydrogels is provided, each group of ANF / PAA / X hydrogels is stacked on the layered hydrogel in order of impedance capacity from low to high.

[0016] Furthermore, in S3, the freezing method is unidirectional freezing, ensuring that the freezing starts from the layered hydrogel structure, and the freezing temperature is -10°C to -60°C.

[0017] Furthermore, in S1 and S2, the concentration of aramid nanofibers in the aramid nanofiber dispersion is 5 to 10 mg / g; and in S2, the concentration of polyamic acid PAA in the polyamic acid PAA dispersion is 30 to 100 mg / g.

[0018] Furthermore, in S3, the thermal imidization treatment method is: under a nitrogen or argon protective atmosphere, 100° C. for 1 hour, 300° C. for 2 hours, and the heating rate is not higher than 3° C. / min.

[0019] (ii) The present invention also provides an aerogel having high electromagnetic shielding and high electromagnetic absorption properties prepared by the preparation method described above.

[0020] Beneficial effects:

[0021] (1) The present invention uses vacuum filtration technology to prepare conductive two-dimensional nanomaterials and aramid nanofibers into layered structural materials as a high-efficiency electromagnetic shielding structure; aramid nanofibers and polyimide can be used to make hydrogel modules, and impedance gradient structures can be designed and assembled by changing the type and content of absorbing fillers to serve as a high-efficiency absorbing structure; the above two are combined and integrated to prepare an electromagnetic shielding composite material with high absorption, low reflection and high-efficiency shielding characteristics, which solves the problem that existing electromagnetic shielding materials bring about a large amount of electromagnetic wave reflection while achieving electromagnetic wave interference shielding, thereby causing serious secondary pollution;

[0022] (2) The high-absorption and high-shielding electromagnetic shielding aerogel with gradient structure and gradual impedance prepared by the present invention overcomes the problem of secondary pollution caused by electromagnetic wave reflection caused by traditional electromagnetic shielding materials. The flexible and adjustable electromagnetic properties of the absorbing module greatly enhance the designability of the material, which is conducive to the step-by-step absorption of electromagnetic waves.

[0023] (3) In the aerogel material prepared by the present invention, the shielding structure and the absorbing structure are made of the same material and are integrally formed, which has the advantages of strong designability, coordinated material system, and economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the microstructure of the electromagnetic shielding aerogel with impedance gradient prepared in Example 2;

[0025] Figure 2 This is an optical picture of the electromagnetic shielding aerogel prepared in Example 1;

[0026] Figure 3 This is a scanning electron microscope image of the electromagnetic shielding aerogel prepared in Example 1;

[0027] Figure 4 This is an X-band electromagnetic shielding effectiveness diagram of the high absorption and high shielding electromagnetic shielding aerogel prepared in Example 1;

[0028] Figure 5 This is an X-band electromagnetic shielding effectiveness diagram of the multilayer impedance gradient structure high absorption and high shielding electromagnetic shielding aerogel prepared in Example 2;

[0029] Figure 6This is a diagram of the X-band electromagnetic shielding effectiveness of the electromagnetic shielding film prepared in Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.

[0032] Example 1

[0033] This embodiment provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0034] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0035] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0036] (2) Preparation of polyamic acid PAA dispersion:

[0037] 3.9 g of 4,4'-diaminodiphenyl ether was added to 60 ml of dimethylacetamide and stirred until completely dissolved, and then 6.1 g of 4,4'-biphenyl ether dianhydride was added and stirred for 4 h. After washing with an excess of deionized water to remove polymer impurities, the solid was dried at 40 ° C for 12 h to finally obtain a white PAA polymer.

[0038] 1.2 g of PAA was weighed and dissolved in 12 g of deionized water, and 1 ml of triethylamine was measured using a micro-pipette. After stirring for 3 hours, a 100 mg / ml PAA aqueous dispersion was obtained.

[0039] (3) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0040] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0041] (4) Preparation of ANF / PAA / X hydrogel with impedance characteristics:

[0042] Aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion were mixed to prepare ANF / PAA hydrogel with a solid content of 1 wt% (the mass ratio of ANF to PAA was 1:1), and the absorber MXene was added and stirred evenly to obtain ANF / PAA / MXene hydrogel. The mass of MXene in the hydrogel was the same as the mass of ANF+PAA solids, and the thickness of the hydrogel was 0.5 cm.

[0043] (5) Preparation of high absorption electromagnetic shielding aerogel:

[0044] The ANF / MXene layered hydrogel was placed in a mold with the ANF surface facing up, and the ANF / PAA / MXene hydrogel was placed above the ANF surface for 15 minutes to allow the two to fully contact and fuse; then it was placed on a -40℃ freezing platform for unidirectional freezing, and then freeze-dried (-40℃, 48h) to obtain MXene / ANF / PAA aerogel; then, under an argon protective atmosphere, 100℃ for 1h, 300℃ for 2h, and the heating rate was 3℃ / min. Finally, the imidization was completed to obtain a high-absorption and high-shielding MXene / ANF / PI electromagnetic shielding aerogel.

[0045] Example 2

[0046] This embodiment provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0047] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0048] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0049] (2) Preparation of polyamic acid PAA dispersion:

[0050] 3.9 g of 4,4'-diaminodiphenyl ether was added to 60 ml of dimethylacetamide and stirred until completely dissolved, and then 6.1 g of 4,4'-biphenyl ether dianhydride was added and stirred for 4 h. After washing with an excess of deionized water to remove polymer impurities, the solid was dried at 40 ° C for 12 h to finally obtain a white PAA polymer.

[0051] 1.2 g of PAA was weighed and dissolved in 12 g of deionized water, and 1 ml of triethylamine was measured using a micro-pipette. After stirring for 3 hours, a 100 mg / ml PAA aqueous dispersion was obtained.

[0052] (3) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0053] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2 ), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0054] (4) Preparation of ANF / PAA / X hydrogel with impedance characteristics:

[0055] Aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion were mixed to prepare three groups of ANF / PAA hydrogels with a solid content of 1 wt% (the mass ratio of ANF to PAA was 1:1). Different amounts of absorber MXene were added to the three groups of ANF / PAA hydrogels and stirred evenly to obtain three groups of ANF / PAA / MXene hydrogels with different impedance characteristics, all with a thickness of 0.5 cm.

[0056] Among them, in the three groups of ANF / PAA / MXene hydrogels, the solid mass ratios of MXene to ANF+PAA were 2:1, 1:1 and 1:2, respectively, and were recorded as group a, group b and group c.

[0057] (5) Preparation of high absorption electromagnetic shielding aerogel:

[0058] Place the ANF / MXene layered hydrogel ANF face upward in the mold, place the c group ANF / PAA / MXene hydrogel on top of the ANF face, then place the b group ANF / PAA / MXene hydrogel on top of the c group, and finally place the a group ANF / PAA / MXene hydrogel on top of the b group, and stack them for 15 minutes to allow each stacking surface to fully contact and fuse; then place it on a -40℃ freezing platform for unidirectional freezing, and then freeze-dry (-40℃, 48h) to obtain the MXene / ANF / PAA aerogel; then, in an argon protective atmosphere, 100℃ for 1h, 300℃ for 2h, and the heating rate is 3℃ / min. Finally, the imidization is completed to obtain a high-absorption and high-shielding MXene / ANF / PI electromagnetic shielding aerogel with a gradient structure and gradual impedance change, which is conducive to the step-by-step absorption of electromagnetic waves. Its structure is referenced Figure 1 shown.

[0059] Example 3

[0060] This embodiment provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0061] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0062] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0063] (2) Preparation of polyamic acid PAA dispersion:

[0064] 3.9 g of 4,4'-diaminodiphenyl ether was added to 60 ml of dimethylacetamide and stirred until completely dissolved, and then 6.1 g of 4,4'-biphenyl ether dianhydride was added and stirred for 4 h. After washing with an excess of deionized water to remove polymer impurities, the solid was dried at 40 ° C for 12 h to finally obtain a white PAA polymer.

[0065] 1.2 g of PAA was weighed and dissolved in 12 g of deionized water, and 1 ml of triethylamine was measured using a micro-pipette. After stirring for 3 hours, a 100 mg / ml PAA aqueous dispersion was obtained.

[0066] (3) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0067] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2 ), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0068] (4) Preparation of ANF / PAA / X hydrogel with impedance characteristics:

[0069] Aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion were mixed to prepare ANF / PAA hydrogel with a solid content of 1 wt% (the mass ratio of ANF to PAA was 1:1), and the absorber MXene was added and stirred evenly to obtain ANF / PAA / MXene hydrogel. The mass of MXene in the hydrogel was the same as the mass of ANF+PAA solids, and the thickness of the hydrogel was 0.5 cm.

[0070] (5) Preparation of high absorption electromagnetic shielding aerogel:

[0071] The ANF / graphene layered hydrogel was placed in a mold with the ANF surface facing up, and the ANF / PAA / MXene hydrogel was placed above the ANF surface for 15 minutes to allow the two to fully contact and fuse; then it was placed on a -40℃ freezing platform for unidirectional freezing, and then freeze-dried (-40℃, 48h) to obtain graphene / ANF / PAA / MXene aerogel; then, under an argon protective atmosphere, 100℃ for 1h, 300℃ for 2h, and the heating rate was 3℃ / min. Finally, the imidization was completed to obtain a highly absorbing and highly shielding graphene / ANF / PI / MXene electromagnetic shielding aerogel.

[0072] Example 4

[0073] This embodiment provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0074] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0075] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0076] (2) Preparation of polyamic acid PAA dispersion:

[0077] 3.9 g of 4,4'-diaminodiphenyl ether was added to 60 ml of dimethylacetamide and stirred until completely dissolved, and then 6.1 g of 4,4'-biphenyl ether dianhydride was added and stirred for 4 h. After washing with an excess of deionized water to remove polymer impurities, the solid was dried at 40 ° C for 12 h to finally obtain a white PAA polymer.

[0078] 1.2 g of PAA was weighed and dissolved in 12 g of deionized water, and 1 ml of triethylamine was measured using a micro-pipette. After stirring for 3 hours, a 100 mg / ml PAA aqueous dispersion was obtained.

[0079] (3) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0080] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2 ), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0081] (4) Preparation of ANF / PAA / X hydrogel with impedance characteristics:

[0082] Aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion were mixed to prepare ANF / PAA hydrogel with a solid content of 1 wt% (the mass ratio of ANF to PAA was 1:1), and the absorber graphene was added and stirred evenly to obtain ANF / PAA / graphene hydrogel. The mass of graphene in the hydrogel was the same as the mass of ANF+PAA solids, and the thickness of the hydrogel was 0.5 cm.

[0083] (5) Preparation of high absorption electromagnetic shielding aerogel:

[0084] The ANF / graphene layered hydrogel was placed in a mold with the ANF surface facing up, and the ANF / PAA / graphene hydrogel was placed above the ANF surface for 15 minutes to allow the two to fully contact and fuse; then it was placed on a -40℃ freezing platform for unidirectional freezing, and then freeze-dried (-40℃, 48h) to obtain graphene / ANF / PAA aerogel; then, under an argon protective atmosphere, 100℃ for 1h, 300℃ for 2h, and the heating rate was 3℃ / min. Finally, the imidization was completed to obtain a high-absorption and high-shielding graphene / ANF / PI electromagnetic shielding aerogel.

[0085] Example 5

[0086] This embodiment provides an integrated preparation method of aerogel with high electromagnetic shielding and high electromagnetic absorption performance, comprising the following steps:

[0087] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0088] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0089] (2) Preparation of polyamic acid PAA dispersion:

[0090] 3.9 g of 4,4'-diaminodiphenyl ether was added to 60 ml of dimethylacetamide and stirred until completely dissolved, and then 6.1 g of 4,4'-biphenyl ether dianhydride was added and stirred for 4 h. After washing with an excess of deionized water to remove polymer impurities, the solid was dried at 40 ° C for 12 h to finally obtain a white PAA polymer.

[0091] 1.2 g of PAA was weighed and dissolved in 12 g of deionized water, and 1 ml of triethylamine was measured using a micro-pipette. After stirring for 3 hours, a 100 mg / ml PAA aqueous dispersion was obtained.

[0092] (3) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0093] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2 ), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0094] (4) Preparation of ANF / PAA / X hydrogel with impedance characteristics:

[0095] Aramid nanofiber (ANF) dispersion and polyamic acid PAA dispersion were mixed to prepare three groups of ANF / PAA hydrogels with a solid content of 1 wt% (the mass ratio of ANF to PAA was 1:1). Different amounts of absorbers (MXene and carbonyl iron) were added to the three groups of ANF / PAA hydrogels and stirred evenly to obtain three groups of hydrogels with different impedance characteristics, all with a thickness of 0.5 cm.

[0096] Among them, in the three groups of hydrogels, the solid mass ratios of MXene+carbonyl iron and ANF+PAA were 10:1, 5:1 and 1:1, respectively, and were recorded as group a, group b and group c.

[0097] (5) Preparation of high absorption electromagnetic shielding aerogel:

[0098] Place the ANF / MXene layered hydrogel in the mold with the ANF surface facing up, place the c group hydrogel on top of the ANF surface, then place the b group hydrogel on top of the c group, and finally place the a group hydrogel on top of the b group, and stack them for 15 minutes to allow each stacking surface to fully contact and fuse; then place it on a -40℃ freezing platform for unidirectional freezing, and then freeze-dry (-40℃, 48h) to obtain MXene / carbonyl iron / ANF / PAA aerogel; then, in an argon protective atmosphere, 100℃ for 1h, 300℃ for 2h, and the heating rate is 3℃ / min. Finally, imidization is completed to obtain a high-absorption and high-shielding MXene / carbonyl iron / ANF / PI electromagnetic shielding aerogel with impedance gradient.

[0099] Comparative Example 1

[0100] This comparative example provides a method for preparing an electromagnetic shielding film, comprising the following steps:

[0101] (1) Preparation of aramid nanofiber (ANF) dispersion:

[0102] 1 g of aramid fiber was mixed with a dimethyl sulfoxide solution (500 ml) containing 1.5 g of potassium hydroxide, and stirred for one week to decompose the aramid fiber to form nano-aramid fiber. After repeated washing with deionized water, a 5 mg / g ANF aqueous dispersion was prepared.

[0103] (2) Preparation of lamellar hydrogels with electromagnetic shielding properties:

[0104] The aramid nanofiber aqueous dispersion obtained in step (1) was vacuum filtered through a microporous filter membrane to form an aramid nanofiber hydrogel (ANF surface density of 0.8 mg / cm 2 ), and then add MXene suspension (the mass ratio of MXene to aramid nanofibers is 6:1) and continue vacuum filtration to obtain ANF / MXene layered hydrogel.

[0105] (3) Preparation of electromagnetic shielding film:

[0106] The ANF / MXene layered hydrogel was placed in a mold with the ANF side facing up, and then placed on a -40°C freezing platform for unidirectional freezing, and then freeze-dried (-40°C, 48h) to obtain a MXene / ANF electromagnetic shielding film.

[0107] Effect test

[0108] The aerogel materials prepared in Examples 1 to 2 and Comparative Example 1 were subjected to electromagnetic shielding effect tests and electromagnetic absorption effect tests.

[0109] Test method:

[0110] The aerogel samples prepared in Examples 1 to 2 and Comparative Example 1 were cut into rectangular blocks of 22.84*10.13 mm, and the S parameters of the aerogels in the X-band were tested using a Ceyear vector network tester. The S parameters were converted into the shielding effectiveness of the aerogels by calculation. The specific calculation method is as follows:

[0111] R=|S 11 | 2 =|S 22 | 2

[0112] T=|S 21 | 2 =|S 12 | 2

[0113] SE T =SE A +SE R

[0114] SE R = -10log(1-R)

[0115]

[0116] Test results: Test results refer to Figures 4 to 6 ,

[0117] Depend on Figure 4 It can be seen that the average electromagnetic shielding effectiveness of the aerogel sample prepared in Example 1 reaches 52.5 dB, and the absorption efficiency SE A Reaching an average of 49dB.

[0118] Depend on Figure 5 It can be seen that the average electromagnetic shielding effectiveness of the three-layer impedance gradient structure aerogel sample prepared in Example 2 reaches 56.5dB, and the absorption efficiency SE A Reaching an average of 56dB.

[0119] Depend on Figure 6 It can be seen that the average electromagnetic shielding effectiveness of the aerogel sample prepared in Comparative Example 1 is only 39.6 dB, and the average absorption efficiency SEA is only 24 dB.

[0120] Therefore, the electromagnetic shielding performance of the aerogel material prepared by the present invention can reach more than 50 dB, and the absorption efficiency accounts for more than 90% of the total efficiency, and the electromagnetic shielding performance of Examples 2 and 5 is better than that of Examples 1, 3 and 4. The reason is that the design and construction of the multi-layer impedance gradient structure allows more electromagnetic waves to enter the material and be absorbed and lost.

[0121] In summary, the aerogel material prepared according to the method of the present invention has excellent electromagnetic shielding performance and electromagnetic absorption performance, which solves the problem that the existing electromagnetic shielding materials bring a large amount of electromagnetic wave reflection while achieving electromagnetic wave interference shielding, thereby causing serious secondary pollution. It is a new type of electromagnetic shielding flexible composite material with high absorption, low reflection and high-efficiency shielding characteristics, and has good mechanical properties, ultra-high broadband electromagnetic wave absorption capacity and high-efficiency electromagnetic shielding performance, as well as excellent heat insulation, sound absorption and other functions, and is suitable for applications in building protection, electronic equipment and aerospace fields.

[0122] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance, characterized in that: The following steps are involved: S1, vacuum filtering the aramid nanofiber dispersion through a microporous filter membrane to obtain a layered aramid nanofiber hydrogel, then adding a conductive two-dimensional nanosheet material, and continuing vacuum filtering to obtain a layered hydrogel with electromagnetic shielding performance; S2, taking aramid nanofiber dispersion and polyamic acid PAA dispersion to mix to prepare ANF / PAA hydrogel, adding absorber X and stirring evenly to obtain ANF / PAA / X hydrogel with impedance characteristics; the number of ANF / PAA / X hydrogels prepared is greater than one group, and each group of ANF / PAA / X hydrogels has a different solid content and / or an amount of absorber added, so as to form several groups of ANF / PAA / X hydrogels with different impedance characteristics as a gradient impedance module; S3, stacking the layered hydrogel prepared in S1 and the ANF / PAA / X hydrogel prepared in S2, freezing, and then freeze-drying and thermally imidizing to form a high-absorption electromagnetic shielding aerogel; in S3, the ANF surface of the layered hydrogel faces upward, and the ANF surface of the layered hydrogel contacts and fuses with the ANF / PAA / X hydrogel; each group of ANF / PAA / X hydrogels is stacked on the layered hydrogel in order of impedance capacity from low to high.

2. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S1, the conductive two-dimensional nanosheet material is graphene and / or MXene.

3. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S1, the surface density of ANF in the layered aramid nanofiber hydrogel is 0.4-1.2 mg / cm 2 The mass ratio of the conductive two-dimensional nanosheet material to the aramid nanofiber is 1~10:

1.

4. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S2, in the ANF / PAA hydrogel, the solid content is 0.5 wt%-3 wt%, and the mass ratio of ANF to PAA is 1:(0~5); the mass of PAA is not 0.

5. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S2, the absorber X is one or more of graphene, MXene, carbon nanotubes, carbonyl iron and ferrite; the mass ratio of the absorber X to the ANF+PAA solid is (0-10):(1-2); and the mass of the absorber X is not 0.

6. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S3, the freezing method is one-way freezing, and the freezing temperature is -10°C to -60°C.

7. The method for preparing an integrated aerogel having high electromagnetic shielding and high electromagnetic absorption performance according to claim 1, characterized in that: In S1 and S2, the concentration of aramid nanofibers in the aramid nanofiber dispersion is 5-10 mg / g; In the S2, the concentration of the polyamic acid PAA in the polyamic acid PAA dispersion is 30-100 mg / g.

8. An aerogel having high electromagnetic shielding and high electromagnetic absorption performance prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of thickness-controllable novel structure MXene composite film

    CN113293655A

  • MXene-based electromagnetic shielding composite film with conductive gradient structure and preparation method of MXene-based electromagnetic shielding composite film

    CN114133601A

Cited By

  • Anisotropic heterogeneous pore double-layer composite aerogel and preparation method thereof

    CN122340792A